Pemenuhan Hak Restitusi: Upaya Pemulihan Korban Tindak Pidana - Trias Saputra; Yudha Adi Nugraha (KRTHA BHAYANGKARA, 2022)
This study discusses the mechanism, regulation and implementation in the Protection of Witnesses and Victims, especially the problem of crime victims. The forms of protection for victims of crime have been regulated by Law Number 13 of 2006 as amended by Law Number 31 of 2014 concerning Protection of Witnesses and Victims. As an example of a form of protection for victims of crime through efforts to fulfill restitution imposed on perpetrators of crime. The method used in this research is juridical-normative using secondary data or library research with the statute approach through evaluation techniques and argumentation techniques. In this study it was also found that in Law Number 31 of 2014 there was an expansion of the form of protection for victims as a result of a crime, namely through the right of restitution. Arguments that strengthen that there is a need for restitution are also found in the minutes and academic texts in the formation of the legislation.